Effectiveness of active middle ear implant placement methods in pathological conditions: basilar membrane vibration simulation - Lee, Sinyoung; Motegi, Masaomi; Koike, Takuji (Frontiers in Neurology, 2024)
Active middle ear implants (AMEI) amplify mechanical vibrations in the middle ear and transmit them to the cochlea. The AMEI includes a floating mass transducer (FMT) that can be placed using two different surgical approaches: “oval window (OW) vibroplasty” and “round window (RW) vibroplasty.” The OW and RW are windows located on the cochlea. Normally, sound stimulus is transmitted from the middle ear to cochlea via the OW. RW vibroplasty has been suggested as an alternative method due to the difficulty of applying OW vibroplasty in patients with ossicle dysfunction. Several reports compare the advantages of each approach through pre and postoperative hearing tests. However, quantitatively assessing the treatment effect is challenging due to individual differences in pathologies. This study investigates the vibration transmission efficiency of each surgical approach using a finite-element model of the human cochlea. Vibration of the basilar membrane (BM) of the cochlea is simulated by applying the stimulus through the OW or RW. Pathological conditions, such as impaired stapes mobility, are simulated by increasing the stiffness of the stapedial annular ligament. RW closure due to chronic middle ear diseases is a common clinical occurrence and is simulated by increasing the stiffness of the RW membrane in the model. The results show that the vibration amplitude of the BM is larger when the stimulus is applied to the RW compared to the OW, except for cases of RW membrane ossification. The difference in these amplitudes is particularly significant when stapedial mobility is limited. These results suggest that RW vibroplasty would be advantageous, especially in cases of accompanying stapedial mobility impairment. Additionally, it is suggested that transitioning to OW vibroplasty could still ensure a sufficient level of vibratory transmission efficiency when placing the FMT on the RW membrane is difficult due to anatomical problems in the tympanic cavity or confirmed severe pathological conditions around the RW.